Long-term maintenance and public exhibition of deep-sea hydrothermal fauna: The AbyssBox project. (November 2015) - Shillito, Bruce; Ravaux, Juliette; Sarrazin, Jozée; Zbinden, Magali; Sarradin, Pierre-Marie; Barthelemy, Dominique
Abstract: The AbyssBox project aims to provide the first permanent public exhibition of live deep-sea hydrothermal fauna maintained at in situ pressure. AbyssBox is a pressurized aquarium designed to function permanently. Here we present details of the project after the public exhibition functioned for more than three years at Océanopolis aquarium in Brest, France. We also describe the AbyssBox pressure aquarium, and provide data and observations on vent shrimp ( Mirocaris fortunata ) and crabs ( Segonzacia mesatlantica ) that were sampled from 1700 m depth at the Lucky Strike vent field (Mid-Atlantic Ridge) during different cruises. While mortalities exceeded 50% during the first days following sampling, the remaining animals appeared to acclimate fairly well. Some crabs have now been kept for more than 2 years, and some shrimp have spent more than 3 years in captivity. Primarily designed for a public exhibition, the AbyssBox is already used for scientific purposes, since it provides one of the most effective tools for long-term rearing of deep-sea fauna. AbyssBox is a first step towards maintaining a variety of deep-sea fauna year-round at in situ pressure, which will serve both scientific and public interests.